2020
DOI: 10.1371/journal.pone.0238911
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a mobile health intervention on uptake of recommended postnatal care services in Nigeria

Abstract: Studies have linked the large percentage of maternal and neonatal mortality that occur in postnatal period to low uptake of postnatal care (PNC) services. Mobile health (mHealth) intervention through message reminders has resulted in significant increase in antenatal care utilisation in previous studies. However, its use in PNC services’ uptake has not been adequately investigated in Nigeria. This study aimed to evaluate the effect of a mobile health intervention on PNC attendance among mothers in selected pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 29 publications
3
33
0
Order By: Relevance
“…After removing duplicates and initial screening, 154 full-text articles were assessed for eligibility. Following further inspection and quality assessment ( Supplementary Table 3 ), 23 articles were included in this review ( 19 , 23 , 38 58 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing duplicates and initial screening, 154 full-text articles were assessed for eligibility. Following further inspection and quality assessment ( Supplementary Table 3 ), 23 articles were included in this review ( 19 , 23 , 38 58 ).…”
Section: Resultsmentioning
confidence: 99%
“…Outcomes on ANC attendance ( Table 7 ) and PNC attendance ( Table 8 ) were reported in six studies ( 19 , 39 , 45 , 49 , 56 , 58 ) and five studies ( 19 , 23 , 38 , 55 , 58 ), respectively. These studies showed that a variety of mHealth interventions delivered through simple mobile phone voice calls ( 56 ), SMS/voice reminders ( 38 , 39 , 49 , 55 ) or apps/data collection modules ( 19 , 23 , 45 , 58 ) can lead to improved access to ANC and PNC services. A study conducted in Ethiopia where SMS reminders for scheduled visits were sent to health workers demonstrated that women in the intervention health centers were more likely to attend at least four ANC visits ( 58 ).…”
Section: Resultsmentioning
confidence: 99%
“…Given the wide coverage of mobile phone networks, mHealth holds promise as an important delivery tool for healthcare delivery in resource-constrained regions (figure 1). mHealth interventions are in use for diagnosis and management of various infectious diseases including malaria,39 tuberculosis40 and human immunodeficiency virus (HIV)41 and for improving maternal and fetal health42 in several developing countries. Although mHealth interventions are increasingly used for non-communicable diseases,43–45 some studies highlight only a modest impact in non-communicable disease (NCD) control, likely due to limited number of studies and impact on process of care alone 46 47.…”
Section: Discussionmentioning
confidence: 99%
“…The results are consistence with findings that women’s phone ownership and usage is generally associated with better reproductive care indicators [ 41 , 42 ]. Using m-health interventions to strengthen postnatal care has proven benefits [ 43 , 44 ]. The assessment here was only covers one question in SLDHS regarding the ownership of a mobile phone, which may need further information on usage for further inferences.…”
Section: Discussionmentioning
confidence: 99%